Congestive myeloradiculopathy in a patient with Cowden syndrome. Issue 2 (February 2015) - Wu, Teddy Y.; Willoughby, Ernest; Hutchinson, David O.; Brew, Stefan; McGuinness, Ben; Lopes, Rebecca; Love, Donald R.; Roxburgh, Richard H.
Abstract We present a patient with newly diagnosed Cowden syndrome and congestive myeloradiculopathy secondary to spinal dural arteriovenous fistula (SDAVF). This patient illustrates the difficulties that can be encountered in diagnosing SDAVF and emphasises the need to pursue the diagnosis in the appropriate clinical setting, as treatment can lead to significant neurological improvement. To our knowledge this is also the first reported case of an association between Cowden syndrome and SDAVF.